Impact of production practices and sanitary management on the prevalence of Neospora caninum and bluetongue virus in Creole goats from the tropical dry forest of Utcubamba, Peru - Tafur Gutierrez, Lucinda (2024)
OBJECTIVE This study aimed to report the impact of production practices and sanitary management on the prevalence of Neospora caninum (N caninum) and bluetongue virus (BTV) in Creole goats from the tropical dry forest of Utcubamba, Peru. METHODS 354 blood samples were obtained from male and female goats of diverse ages reared under an extensive productive system. The diagnosis of N caninum and BTV was conducted through a commercial ELISA kit (iD.vet) with readings taken on a Bio-Rad iMark microplate reader at 450 nm. Additionally, a survey was conducted with 18 goat producers to categorize them based on social, technical (production, health, reproduction, nutrition, and infrastructure), environmental, and economic factors. RESULTS The overall seroprevalence of N caninum and BTV in goats was 6.21% and 7.06%, respectively, Notably, group II farmers had the highest prevalence rates at 7.69% for N caninum and 23.08% for BTV. This group comprises producers with fewer than 21 goats, while group III includes 14.3% of producers with over 60 goats and better infrastructure. CONCLUSIONS This study confirms the presence of N caninum and BTV in goats of Utcubamba, Peru. Group II displayed the highest prevalence rates, suggesting that herd size and management infrastructure influence disease prevalence. CLINICAL RELEVANCE In the tropical dry forest of Utcubamba, inadequate management of N caninum carrier agents (eg, nondewormed dogs) heightens transmission risk, while the tropical climate supports BTV vectors. Effective diagnosis and health management strategies, including vector control and biosecurity practices, are crucial for ongoing herd health monitoring